2021
DOI: 10.1108/cg-07-2021-0256
|View full text |Cite
|
Sign up to set email alerts
|

Are political connections beneficial or harmful toward firms’ performance? A meta-analysis approach

Abstract: Purpose This study aims to reconcile conflicting empirical results from prior studies on the association between political connections (PCs) and firms’ performance. Furthermore, it investigates whether the contradictory findings were moderated by the different types of both PCs and firms’ performance measures. This study also makes a cross-country comparison of the empirical evidence to provide more insight. Design/methodology/approach This study used meta-analysis to integrate the previous studies’ findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…For example, some empirical evidence has found that PCs enhance a firm financial performance (Ding et al , 2014; Unsal, 2017; Wang et al , 2019; Maaloul et al , 2018; Idris et al , 2020; Joni et al , 2020; Prasetyo and Nasution, 2021). Some reasons articulated for this positive relationship are winning government contracts and concessions, access to external financing (Faccio et al , 2006; Goldman et al , 2013; Sadiq et al , 2019; Preuss and Königsgruber, 2021) and lower tax burdens (Chen et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some empirical evidence has found that PCs enhance a firm financial performance (Ding et al , 2014; Unsal, 2017; Wang et al , 2019; Maaloul et al , 2018; Idris et al , 2020; Joni et al , 2020; Prasetyo and Nasution, 2021). Some reasons articulated for this positive relationship are winning government contracts and concessions, access to external financing (Faccio et al , 2006; Goldman et al , 2013; Sadiq et al , 2019; Preuss and Königsgruber, 2021) and lower tax burdens (Chen et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, these countries face stronger financing constraints, have fewer effective institutions to aid financial contracting and securing property rights, lack adequate collateral and other guarantees against borrowing, resort more often to informal finance, have highly concentrated ownership structures and less efficient markets and face higher business uncertainty and market volatility (Booth et al, 2001;Eldomiaty, 2007). It was found that political connections in both democratic and authoritarian nations tend to have a positive relationship with companies' performance (Prasetyo and Nasution, 2022). Further, strong socially woven political hierarchies and connections may weaken the beneficial properties of shareholder dominance; therefore, firms pursuing their interests in a more decentralized manner may outperform the rest (Allen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…performance and valuation (Fisman, 2001;Shahzad et al, 2021;Prasetyo and Nasution, 2021), accounting performance (Boubakri et al, 2008), quality of earnings (Chaney et al, 2011), government investment decisions (Duchin and Sosyura, 2012;Schoenherr, 2019) and tax liability (Faccio, 2010;Khlif and Amara, 2019), there remains limited insights on potential effects of the political contributions on corporate risk-taking.…”
Section: Introductionmentioning
confidence: 99%
“…Although some past studies have explored the effect of PC on share prices (Brown and Huang, 2020; Child et al , 2021), innovation (Kim, 2018; Krammer and Jimenez, 2020); firm performance and valuation (Fisman, 2001; Shahzad et al , 2021; Prasetyo and Nasution, 2021), accounting performance (Boubakri et al , 2008), quality of earnings (Chaney et al , 2011), government investment decisions (Duchin and Sosyura, 2012; Schoenherr, 2019) and tax liability (Faccio, 2010; Khlif and Amara, 2019), there remains limited insights on potential effects of the political contributions on corporate risk-taking.…”
Section: Introductionmentioning
confidence: 99%